2016
DOI: 10.3122/jabfm.2016.04.160037
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Recommended Chronic Pain Assessment and Management in Primary Care: Does Patient-Centered Medical Home (PCMH) Recognition Make a Difference?

Abstract: Background: Chronic pain (CP) care in the patient-centered medical home (PCMH) model has not been well studied. We assessed whether PCMH recognition is associated with increased provision of key practice recommendations for CP assessment and management.Methods: Chart reviews were completed for 12 primary care practices affiliated with one health system in the Cincinnati Area Research and Improvement Group (CARInG). Recommendations were abstracted and compared based on PCMH status: 3 practices had received prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The current literature on pharmacist engagement in chronic pain management is limited to specialty care settings (eg, palliative care), investigations of patient-centered medical home designation, or descriptive reports. 15,16,[22][23][24][25] To our knowledge, this is the first published study of the impact of a pharmacist-led intervention focused on comprehensive chronic pain management in a family medicine setting. The purpose of this study was to evaluate the impact of a previsit pharmacist review of highrisk patients treated with opioids for chronic noncancer pain for compliance with CDC recommendations at a family medicine residency clinic.…”
mentioning
confidence: 99%
“…The current literature on pharmacist engagement in chronic pain management is limited to specialty care settings (eg, palliative care), investigations of patient-centered medical home designation, or descriptive reports. 15,16,[22][23][24][25] To our knowledge, this is the first published study of the impact of a pharmacist-led intervention focused on comprehensive chronic pain management in a family medicine setting. The purpose of this study was to evaluate the impact of a previsit pharmacist review of highrisk patients treated with opioids for chronic noncancer pain for compliance with CDC recommendations at a family medicine residency clinic.…”
mentioning
confidence: 99%
“…Most studies were performed in primary care clinics, university-affiliated centers, or Veterans Affairs hospitals (see Table 1). Eleven studies reported details of 696 health care providers whose patient medical records were reviewed (Anderson et al, 2016; Cox, Tak, Cochella, Leishman, & Gunning, 2018; Elder et al, 2016; Elder, Simmons, Regan, & Gerrety, 2012; Jacobs et al, 2016; Lange et al, 2015; Liebschutz et al, 2017; Quanbeck et al, 2018; Salinas et al, 2012; Wong et al, 2019; Yanni et al, 2008). Medical records were reviewed for 22,512 patients with CNCP.…”
Section: Resultsmentioning
confidence: 99%
“…One goal of the Affordable Care Act (ACA) was to encourage a more integrated and coordinated approach across all kinds of care, including the use of the so-called Patient Centered Medical Homes, to emphasize multi-disciplinary team treatment and chronic disease management. 67 Although small studies suggest that Patient Centered Medical Homes may enhance the quality of chronic pain and addiction in certain primary care settings, 68 there is little evidence that the ACA did much to support primary care more broadly. Other ACA innovations relating to primary care also have yet to have shown significant results.…”
Section: The Treatment Of Pain In In the Specialty Arena Versus mentioning
confidence: 99%